2017
DOI: 10.1176/appi.ajp.2016.16070792
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Behavioral Interventions in Buprenorphine Maintenance Treatment: A Review

Abstract: Objective Although counseling is a required part of office-based buprenorphine treatment of opioid use disorders, the nature of what constitutes appropriate counseling is unclear and controversial. We review the existing literature on the role, nature, and intensity of behavioral interventions in office-based buprenorphine treatment. Method Review of randomized controlled studies testing the efficacy of adding a behavioral intervention to buprenorphine maintenance treatment. Results Four key studies showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
126
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 180 publications
(128 citation statements)
references
References 71 publications
2
126
0
Order By: Relevance
“…While the added benefit of behavioral interventions in the delivery of MAT is still in question (e.g., 60), many providers and researchers consider adjunctive psychosocial counseling with MAT as the gold standard (59, 61). Counseling during the early phases of MAT may enhance patients’ motivation while later focus can shift to improving coping and relapse prevention skills (59).…”
Section: Discussionmentioning
confidence: 99%
“…While the added benefit of behavioral interventions in the delivery of MAT is still in question (e.g., 60), many providers and researchers consider adjunctive psychosocial counseling with MAT as the gold standard (59, 61). Counseling during the early phases of MAT may enhance patients’ motivation while later focus can shift to improving coping and relapse prevention skills (59).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive behavioral therapy (Kumari et al, 2016; Moore et al, 2016) and contingency management (Ling et al, 2013) have previously shown effectiveness with community-based samples and may have potential – if culturally adapted to address the specific substance use and mental health needs of criminal justice-involved African American men. Finally, while medication-based interventions have shown some efficacy (Carroll & Weiss, 2017) and effectiveness (Damian et al, 2017), compared to Whites, African Americans are disproportionately underrepresented in pharmacotherapy studies (Hansen et al, 2016; Mitchell et al, 2016). More research is needed to assess the acute and long-term effectiveness of buprenorphine, methadone, and potential barriers in accessing related treatments among African American men re-entering the community from prison.…”
Section: Discussionmentioning
confidence: 99%
“…The principal limitation of MAT is high drop-out rates and subsequent relapse to opioid use. For buprenorphine and methadone maintenance treatments, retention rates at 1 year are typically less than 50% [7, 8]. Retention rates for injectable sustained-release naltrexone are even lower [2730].…”
Section: Pharmacological Treatment Of Oudmentioning
confidence: 99%